Relational Changes During Role Transitions: The Interplay of Efficiency and Cohesion - Jonczyk, Claudia D.; Lee, Yonghoon G.; Galunic, Charles D.; Bensaou, Ben M. (Academy of Management Journal, 2016)
This study looks at what happens to the collection of relationships (network) of service professionals during a role transition (promotion to a management role). Our setting is three professional service firms where we examine changes in relations of recently promoted service professionals (auditors, consultants, and lawyers). We take a comprehensive look at the drivers of two forms of network changes – tie loss and tie gain. Looking backward we examine the characteristics of the contact, the relationship, and social structure and identify which forces are at play in losing ties, revealing an overarching tendency for both cohesion and efficiency forces to play a role. Looking forward, we identify the effect of previous network structures that act as a “shadow of the past” and impact the quality of newly gained relations during the role transitions. Findings demonstrate that role transitions are not only influenced by a few key contacts but that the entire (extant) network of professional relationships shapes the way people reconfigure their workplace relations during a role transition.